Legal Pluralism and the Study of Shari'a Courts - Shahar, Ido (Islamic law and society, 2008)
Abstract Legal pluralism has emerged in the last few decades as a prominent theoretical perspective in socio-legal research. Recently, scholars of Islamic law have begun to employ analytical concepts and theoretical insights drawn from this theoretical framework in their studies of Islamic law and shari'a courts. In this article I argue that the time has come for a systematic assessment of the relevancy of a legal-pluralist perspective for the study of shari'a courts. Specifically, I discuss its potential contribution for understanding relations between shari'a courts and other tribunals, and between qadis affiliated with different madhhabs.